PSYCHOLOGICAL PREPARATION OF A PERSON FOR ABNORMAL COLD WEATHER IN EXTREME SITUATIONS - Abduvokhidov X.A (Western European Studies, 2025)
In this article, people are given recommendations on how to act in case of abnormal cold in extreme situations, and a general idea of how to prepare them mentally
Keywords: Extreme situations; stressfulsituation; anomaly in Greek